The Da'wah Message in an Indonesian Horror Film (Case Studies on Film Pengabdi Setan Using A Semiotics Model Roland Barthes) - Kiki Maulfi Hardiyanti; Muchlis Muchlis (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
The study described a horror film entitled Pengabdi Setan that describes a family that believes in Islam. However, it is said that the family did not follow the true Islamic Friday. With all the weird and creepy things that often happen to his family. In this case, one member of the family is the mother of the devil. It was done to produce offspring. In research for this thesis, researchers formulated the problem as